D = (-2)^3×(3/4-0,25)÷(9/4-7/6)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\left(-2\right)^3.\left(\frac{3}{4}-0,25\right):\left(\frac{9}{4}-\frac{7}{6}\right)\)
\(=-8.\left(\frac{3}{4}-\frac{1}{4}\right):\left(\frac{27}{12}-\frac{14}{12}\right)\)
\(=-8.\frac{1}{2}:\frac{13}{12}\)
\(=-\frac{8}{2}.\frac{13}{12}\)
\(=-\frac{8.13}{2.12}\)
\(=-\frac{2.4.13}{2.4.3}\)
\(=-\frac{13}{3}\)
^_^
a=113/13-(24/7+53/13)=113/13-24/7-53/13=60/13-24/7=396/16
b=(64/9+37/11)-44/9=64/9+37/11-44/9=20/9+37/11=181/33
c=-5/7(2/11+9/11)+15/7=-5/7+15/7=10/7
d=0.7.22/3.20.0.375.5/28=0
e=(6,17+35/9-236/97)(1/3-0.25-1/12)=A.(1/3-1/4-1/12)=A.(1/12-1/12)=A.0=0
e=(6,17 + 3 5/9 - 2 36/97 ) . ( 1/3 - 0,25 - 1/12)=(6,17 + 3 5/9 - 2 36/97 ) .(1/3-1/12-0,25)
=(6,17 + 3 5/9 - 2 36/97 ) .(4/12-1/12-0,25)=(6,17 + 3 5/9 - 2 36/97 ) .(3/12-0,25)
=(6,17 + 3 5/9 - 2 36/97 ) .(1/4-0.25)=(6,17 + 3 5/9 - 2 36/97 ) .(0.25-0.25)
=(6,17 + 3 5/9 - 2 36/97 ) .0=0
Vậy E=0
a/ S = ( - 2/3 + 1) - (7/5 - 0,2) + )7/15 - 1 + 4/3) = - 2/3 + 1 - 7/5 + 1/5 +7/15 - 1 + 4/3 = 2/3 - 6/5 + 7/15 = 10/15 - 18/15 + 7/15 = - 1/15.
b/ S = 0,25 - 9- (- 3/4) - [ - 7/3 + (-9/2)] - 5/6 = 1/4 - 9 + 3/4 + 7/3 + 9/2 - 5/6 = - 8 + 14/6 + 27/6 - 5/6 = - 8 + 6 = - 2
(-2)3 . (\(\frac{3}{4}\) - 0,25) : (\(\frac{9}{4}-\frac{7}{6}\))
= -8 . \(\frac{1}{2}\) : \(\frac{13}{12}\)
= -4 : \(\frac{13}{12}\)
= \(-\frac{48}{13}\)
\(=(\frac{3}{4}-\frac{1}{4})-\frac{7}{3}+\frac{9}{2}-\frac{5}{6}=\frac{1}{2}+\frac{9}{2}-\frac{14}{6}-\frac{5}{6}=5-\frac{19}{6}=\frac{11}{6}\)
Kết bạn nha bạn
Bài làm
\(\frac{3}{4}-0,25-\left(\frac{7}{3}+\frac{-9}{2}\right)-\frac{5}{6}\)
\(=\frac{3}{4}-\frac{1}{4}-\left(\frac{14}{6}+\frac{-27}{6}\right)-\frac{5}{6}\)
\(=\frac{1}{2}+\frac{13}{6}-\frac{5}{6}\)
\(=\frac{3}{6}+\frac{13}{6}-\frac{5}{6}\)
\(=\frac{11}{6}\)
# Học tốt #
\(D=\left(-2\right)^3x\left(\frac{3}{4}-0,25\right):\left(\frac{9}{4}-\frac{7}{6}\right)\)
\(D=-8.\frac{1}{2}:\frac{13}{12}\)
\(D=-4:\frac{13}{12}\)
\(D=\frac{-48}{13}\)